2013
DOI: 10.1158/1535-7163.mct-13-0066
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Sensitizes Colon Cancer Cells to Antitumor Activity of ABT-263

Abstract: Apigenin is an edible plant-derived flavonoid that shows modest anti-tumor activities in vitro and in vivo. Apigenin treatment resulted in cell growth arrest and apoptosis in various types of tumors by modulating several signaling pathways. In the present study, we evaluated interactions between apigenin and ABT-263 in colon cancer cells. We observed a synergistic effect between apigenin and ABT-263 on apoptosis of colon cancer cells. ABT-263 alone induced limited cell death while upregulating expression of Mc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 42 publications
1
70
0
Order By: Relevance
“…Moreover, apigenin significantly decreased the level of Her2/neu, a protein involved in growth factor signaling, which indicated a reduction in breast cancer cell proliferation in apigenin-treated mice 33. Apigenin also displayed significant antitumor activity in human colon cell implanted nude mice 34,35. The anti-metastatic activity of apigenin has also been reported in an orthotopic colorectal nude mouse model 36.…”
Section: Role Of Apigenin In Cancer Preventionmentioning
confidence: 84%
“…Moreover, apigenin significantly decreased the level of Her2/neu, a protein involved in growth factor signaling, which indicated a reduction in breast cancer cell proliferation in apigenin-treated mice 33. Apigenin also displayed significant antitumor activity in human colon cell implanted nude mice 34,35. The anti-metastatic activity of apigenin has also been reported in an orthotopic colorectal nude mouse model 36.…”
Section: Role Of Apigenin In Cancer Preventionmentioning
confidence: 84%
“…Apigenin substantially upregulates CD26/DPPIV on human colorectal cancer HT-29 and HRT-18 cells to inhibit metastasis [81]. Synergistic interaction between apigenin and ABT-263, a BH3 mimetic inhibitor of the Bcl-2 family, was more potent than apigenin or ABT-263 alone in inhibiting tumor growth in xenograft tumors of colon cancer cells [82]. …”
Section: 0 Effect Of Apigenin In Various Human Cancersmentioning
confidence: 99%
“…Apigenin (4â€Č,5,7‐trihydroxyflavone) belongs to the flavonoids family and commonly present in herbs, fruits, and vegetables (Perrott, Wiley, Desprez, & Campisi, ). Some studies with in vitro and in vivo models have already shown chemopreventive and chemotherapeutic effects of apigenin (Shao et al, ; Tong & Pelling, ). Anticarcinogenic effects of apigenin are exerted by the regulation of multiple cellular processes such as response to oxidative stress and DNA damage, activation of programmed cell death pathways such as autophagy and apoptosis, inhibition of inflammation, angiogenesis, and cell proliferation, in several human cancer cells (Sung, Chung, & Kim, ).…”
Section: Some Common Phytochemicals With Chemopreventive and Chemothementioning
confidence: 99%